Penerapan Pembelajaran Keterampilan Pemecahan Masalah Sosial Untuk Meningkatkan Kualitas Pembelajaran PKn di SD Kecamatan Lembah Segar Kota Sawahlunto - Reinita , (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
One of the tasks of primary schools teachers in improving the quality learning of PKn is working to achieve the purpose of PKn learning. The purpose of PKn learnimg that accordance with the curriculum of PKn in elementeary schools are:1) in order for students to have the ability of critical thinking, creatively, and also rational in citizen issues responded, 2) participate actively and responsibly, the act intelligently in the activities of society, nation, and state, 3) developing in positive and democratic self according to form of Indonesian character to able to live together with other people, 4) integrate with other peoples in the world scene directly or indirectly by making use of information and communication technology. For successful teachers achieve the PKn learning, teachers need to understand and perform the duties and functions of the teaching of PKn based on a new paradigm,that is developing the intelligence of active participation, students responsibilities as citizens. By having an understanding of the duties and functions of the teachers in PKn, the teachers will certainly always attempt to choose and use appropriate leraning model with aspects of learning PKn. On of learning models that are considered appropriate to enhance aspects of attitudes and skills is model of social problem solving skills. The model aims at forming students becoming individuals who are able to solve social problems in everyday life. Measures the application of the model social problem solving skills are : 1) identify the public policy issues in the community, 2) select an issues to be examined in the class, 3) Gather information related issues, 4) develop a portfolio class, 5) present the portfolio, 6) performs reflection a learning experience